Analysis Of Home Yard Utilization Based On The Green Economy Concept For Enhancing Community Economic Welfare From The Perspective Of Islamic Economics - Firqotus Sa’idah; Syamsul Hilal; Madnasir Madnasir (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This research is motivated by population growth which is a trigger factor for the exploitation of natural resources and narrowing land supplies. This research aims to analyze and find out how to apply yard land with the green economy concept in improving the community economy from an Islamic economic perspective in the city of Bandar Lampung. The method in this research uses qualitative methods. This type of research is field research. The data source in this research is primary data through observation and interviews. The results of this research are the use of yard land by KWT in Bandar Lampung City who have implemented agriculture with an environmentally friendly system, by planting using animal waste fertilizer and kitchen waste, using a planting system. traditional and low carbon hydroponics.  Then, from a sharia economic perspective, the application of yard land has fulfilled the basic requirements that are measured in Islam, namely hidzu al din, protecting religion, one of which is by protecting the environment, processing kitchen waste into fertilizer so that it does not pollute the environment, hifdzu al aql through training activities that can increase the creativity of members. farmer group, hidzu al nafs KWT takes care of the yard so that it is clean, comfortable, healthy and beautiful which can calm the souls of those who see it, hidzu al nafs a clean and maintained environment can maintain human health from generation to generation and hidzu al mal managing and utilizing owned assets such as yard land